Petrography and Geochemical Relationships of the Ultramafic Rocks in Galalah area within Erbil Governorate, NE Iraq - Al-Jubury, Harth E.; Tamr Agha, Mazin Y.; Aqrawi, Ahmed M. (Iraqi Journal of Science, 2023)
The current research to study the petrography, mineralogy and geochemical relationships of the ultramafic rocks in the Galalah area within Erbil Governorate, at the Unstable Shelf in the Imbricate Zone, to determine the origin of the ultramafic rocks.      Dunite and Harzburgite are the most abundant rock bodies in the study area, and they represent most of the outer surface exposure of the ultramafic rock aggregates. The dunite rocks are characterized by pale brown color on the altered surface that is broken into olive green and dark green lithic. Dunite represents a homogenous lithologic feature that mainly consists predominately of olivine with accessory spinel and traces of orthopyroxene. While the harzburgite appears as a massive rock body consisting of olivine, orthopyroxene, and clinopyroxene. These rocks are mainly characterized by alteration to serpentinite, with accessory chromian spinel, secondary magnetite, chlorite, and talc.The studied ultramafic rocks are predominately rich in ferromagnesian minerals of less silica content, and other major elements affected by serpentinization are causing the deviation of elements. They have a strong decrease in sodium and calcium oxides relative to MgO and verified the silica and alumina with MgO and a slight increase in iron oxide.The low values of TiO2 in dunite and harzburgite are characteristic property of the Alpine type ophiolites during the primary process of the mantle in its upper part, before the tectonic emplacement of the ultramafic rocks, and also due to partial melting degree for the asthenospheric mantle. The MREE depletion relative to HREE and LREE may be attributed to the hornblende absence and the presence of olivine and pyroxenes minerals and/or to the source rock features.The U-shaped patterns of REE and their ratios are typical properties of ophiolitic ultramafic rocks, which are compatible with the supra-subduction zone. During the partial melting, the negative anomalies of Nb in ultramafic rocks with sequestration of the Nb concentration by sphene and ilmenite in various types of the source rocks have also been attributed to the crust contamination. These are also characterized by island arc conditions, and its depletion in the studied rocks may indicate the fore-arc tectonic environments